ANALISIS PENERAPAN APLIKASI DIGITAL GUNA MENINGKATKAN KINERJA KARYAWAN PADA PT PLN (PERSERO) UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) BINJAI - Lisa Ramahdani; Dinda Karunia Putri; Zainarti (JURNAL ILMIAH RESEARCH STUDENT, 2023)
PT PLN (Persero) UP3 Binjai is one of the PLN units responsible for the electricity distribution function. In the world of electricity, its position is very important, namely as an interface with customers. The aim of this research is to determine the effect of implementing digital applications to improve employee performance at PT PLN (Persero) UP3 Binjai. Using qualitative methods such as interviews and observations as well as literature review, interviews were conducted with PLN UP3 Binjai employees. The results obtained from this research are that updates on technological developments in the world of work, especially PLN UP3 Binjai employees, are very helpful in achieving the company's goals. The implementation of digitalization in the form of applications to make employee work easier is a form of facing competition in the reform era. So that the implementation of digital applications has a positive impact on the performance of company employees.